Resource optimization through process re-engineering of inhalational therapy unit at a tertiary care public hospital - Choudhary, Abdul Hakim; Palaskar, Manisha K.; Kausar, Mohammad; R., Mahesh; Sharma, D. K. (International Journal of Research in Medical Sciences, 2019)
Background: Salaries, supplies and machinery account for bulk of public funding necessitating efficient utilisation. Studies suggest that process re-engineering helps improve cost, quality, service, and speed. Disbanded once and re-commissioned, a centralized Inhalational Therapy Unit (ITU) banked and provided portable mechanical ventilators to the inpatient wards. A demand for new ventilators from ITU led to the present study involving its critical review and cost analysis. Methods: An interventional study was conducted at a large tertiary care public hospital in India from April 2015 to June 2015. Critical review of process of providing portable ventilators and cost analysis were conducted. Review of records of and interview with ITU personnel and nursing staff were carried out. Fundamental rethinking and radical redesign of the process was done with attention to human resource, costs, space and actual medical equipment utilization. Two fundamental questions of process re-engineering were deliberated upon: “Why do we do what we do?” “And why do we do it the way we do?” Fundamental rethinking for new process was organized around the outcome. Results: Average utilization coefficient was 6.2% (3.3% to 12.1%). Ventilators utilized per day were 1.43. Expenditure on salaries was INR 315000 per month and INR 10500 per day. Low utilization offered low value for expenses incurred. All activities in ITU focused on “provision of ventilators” (outcome) and the old rule was, “If one needed a ventilator one must contact ITU”. Since nurses were using the “outcome” and performed activities of arranging, they were handed-over the ventilators (based on utilisation patterns). ITU was disbanded, human resource and space were re-allocated to various hospital areas (costs tied were done away with) with no adverse effect on hospital functioning. Conclusions: Process re-engineering led to improved healthcare delivery, curtailed delays in hospital processes, optimised costs involved in human resources and medical equipment.